Grand designs and visions of unity : the Atlantic powers and the reorganization of Western Europe, 1955-1963 - Giauque, Jeffrey Glen (New Cold War history., 2002)
In the late 1950s, against the unfolding backdrop of the Cold War, American and European leaders began working to reshape Western Europe. Focusing on the four largest Atlantic powers - Britain, France, Germany and the United States - Giauque explores these early stages of European integration.